Situation of non-communicable diseases in Peru during the COVID-19 pandemic - Hancco-Saavedra, Jorge Arturo (2023)
In Peru, noncommunicable diseases represent a high rate of its burden of disease. According to the Demographic and Family Health Survey, from 2016 to 2021, the percentage of people aged 15 and older with a medical diagnosis of arterial hypertension has increased by 4.5 percentage points and on average 65.5% take medication for their disease. The percentage of people aged 15 and older with a medical diagnosis of diabetes increased by 2 percentage points and on average 71.2% take medication for their disease. The preventive care services reduction due to COVID-19 pandemic in Peru shows the need to establish strategies oriented to the use of information and communication technologies, reinforce health education programs, guarantee access to pharmaceuticals and medical devices, adequately remunerated human resources and strengthen NCD epidemiological surveillance programs that contribute to decision making.